The Effect of Ethnocentrism and Image of Asian Industrialised Countries on Perceived Relative Quality - Sulhaini, Sulhaini; Mulyono, Lalu Edy Herman (International Research Journal of Business Studies, 2014)
The study examined the effects of consumer ethnocentrism and country image on perceived relative quality. The respondents of the study were consumers at a shopping mall in Mataram, Indonesia. They compared the quality of televisions from three industrialised Asian countries, i.e. Japan, South Korea and China, to those from Indonesia. The result of the study was that image of those countries has a significant effect on perceived relative quality. Indonesian consumers perceived televisions from those countries to be more favourable in terms of quality compared to Indonesian televisions. Indonesian consumers have a similar perception on the quality of televisions made in those main Asian countries relative to those of Indonesia. The image of those countries is favourable leading to a better perception on quality of televisions made in the countries relative to domestically made. Domestic consumers view that those countries have better capabilities in producing higher quality televisions. However, consumer ethnocentrism do not lead them to negatively perceive the quality of imported televisions. Indeed, the image of those countries has a greater role in Indonesian consumers’ quality evaluation. The result calls for a substantial improvement in quality of domestically made televisions.